Preoperative physiotherapy and short-term functional outcomes of primary total knee arthroplasty - Ismail, Mohd Shukry; Sharifudin, Mohd Ariff; Ahmad Shokri, Amran; Ab Rahman, Shaifuzain (Singapore Medical Association, 2016)
Physiotherapy is an important part of rehabilitation following arthroplasty, but the impact of preoperative physiotherapy on functional outcomes is still being studied. This randomised controlled trial evaluated the effect of preoperative physiotherapy on the short-term functional outcomes of primary total knee arthroplasty (TKA). 50 patients with primary knee osteoarthritis who underwent unilateral primary TKA were randomised into two groups: the physiotherapy group (n = 24), whose patients performed physical exercises for six weeks immediately prior to surgery, and the nonphysiotherapy group (n = 26). All patients went through a similar physiotherapy regime in the postoperative rehabilitation period. Functional outcome assessment using the algofunctional Knee Injury and Osteoarthritis Outcome Score (KOOS) scale and range of motion (ROM) evaluation was performed preoperatively, and postoperatively at six weeks and three months. Both groups showed a signi cant difference in all algofunctional KOOS subscales (p < 0.001). The mean score difference at six weeks and three months was not signi cant in the sports and recreational activities subscale for both groups (p > 0.05). Signi cant differences were observed in the time-versus-treatment analysis between groups for the symptoms (p = 0.003) and activities of daily living (p = 0.025) subscales. No signi cant difference in ROM was found when comparing preoperative measurements and those at three months following surgery, as well as in time-versus- treatment analysis (p = 0.928). Six-week preoperative physiotherapy showed no signi cant impact on short-term functional outcomes (KOOS subscales) and ROM of the knee following primary TKA.